Modeling runoff response to land-use changes using the SWAT model in the Mundaú watershed, Brazil - Farias, Carolyne Wanessa Lins de Andrade; Montenegro, Suzana Maria Gico Lima; Montenegro, Abelardo Antônio de Assunção; Lima, José Romualdo de Sousa; Srinivasan, Raghavan; Jones, Charles Allan (Journal of Environmental Analysis and Progress, 2020)
Land-use change has a significant influence on runoff process of any watershed, and the deepening of this theme is essential to assist decision making, within the scope of water resources management. The study was conducted for Mundaú River Basin (MRB) using the Soil and Water Assessment Tool (SWAT) model. The study aims to assess the issue of land-use change and its effect on evapotranspiration, surface runoff, and sediment yield. Input data like land use, topography, weather, and soil data features are required to undertake watershed simulation. Two scenarios of land use were analyzed over 30 years, which were: a regeneration scenario (referring to use in the year 1987) and another scene of degradation (relating to use in the year 2017). Land use maps for 1987 and 2017 were acquired from satellite images. Overall, during the last three decades, 76.4% of forest was lost in the MRB. The grazing land increased in 2017 at a few more than double the area that existed in 1987. Changes in land use, over the years, resulted in an increase of about 37% in the water yield of MRB. Changes have led to increased processes such as surface runoff and sediment yield and in the decrease of evapotranspiration. The spatial and temporal distribution of land use controls the water balance and sediment production in the MRB.